STUDENT ENGAGEMENT UNTUK PEMBELAJARAN YANG MENARIK DAN BERKUALITAS DI BULAN PUASA - Ainur Rosyid (Yayasan Nusantara Hasana Berdikari, 2023)
Student engagement is one of the important factors in learning to create enjoyable and high-quality learning. The issue frequently faced by lecturers or teachers in the classroom is how to encourage students to actively participate in learning, especially during the month of Ramadan fasting. With the characteristics of Generation Z students, the use of web-based or cloud-based applications can be utilized, such as Trello, Padlet, Miro, Kahoot, and Quizzes. To enable the lecturers at Esa Unggul University to provide enjoyable and high-quality learning, the Research and Community Service Department (LPPM) of Esa Unggul University conducts community engagement activities in the form of counseling or sharing sessions. This activity runs well and smoothly, yielding quite positive results as well. This evident can be seen from the evaluation results, which indicate that the scores obtained from the comprehension evaluation are as follows: 34% of participants scored 100, and 29% scored 75. Moreover, 85% of participants are also confident in applying or using these applications for student engagement and teaching assessment in the future. However, the rest are still uncertain, possibly due to their current job not aligning well with the implementation of these applications. The applications most chosen by participants to be used in their classroom learning are Trello with 39%, Padlet with 20%, and Miro with 7%.